A study on the rainfall and landslides along Sarawak road using the antecedent rainfall analysis. - Tay, J.E (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Sarawak is a state known for its high percentage of clayey soil which is overlaid with "weak"strata. The state has experienced many cases of severe landslide occurrences along roads in Sarawak. By using the antecedent rainfall analysis, this study emphasizes on more than 50 cases of landslides which occurred along Sarawak roads in the early 2009. The observations and forecasts present in this paper will provide warning system for the members of public as well as the state's civil defense authority before the occurrence of rainfall-induced landslide.